The Effect of Attachment Styles on Celebrity Worship in K-Pop Fans with Age as a Moderator - Jayanti, Irnawati; Yulianto, Aries (Sebatik, 2025)
The increasing popularity K-Pop in Indonesia has captured the attention of diverse age groups, especially in adolescents and young adults. Fans’ attachment to K-Pop idols can be understood by the concept of celebrity worship. Celebrity worship consists of three levels; from entertainment social, as the low level, intense personal, as the moderate one, and bordeline pathological, as the highest. Adolescents and young adult had differences in celebrity worship, On the other hand, attachment styles develop from childhood to form attachment patterns that occur when a person reach adulthood. There are four types of attachment style, i.e.: fearful, dismissing, preoccupied, and secure. We believe celebrity worship can be affected by attachment styles in adolescent and young adult K-pop fans. This quantitative study aims to investigate the effect of attachment style on celebrity worship, with age as a moderating variable. The study involved adolescent and young adult K-Pop fans, using the Celebrity Attitude Scale (CAS) and the Attachment Style Questionnaire (ASQ) as measurement tools. Data were analyzed using two-way ANOVA. This study found that age moderates the effect of attachment style on celebrity worship. Dismissing attachment styles influenced the entertainment-social dimension in young adults but not in teenagers. These results highlight the importance of the developmental stage in understanding the effect of attachment style on celebrity worship.